ST‐elevation acute myocardial infarction in pregnancy: 2016 update. Issue 6 (13th February 2017) - Ismail, Sahar; Wong, Cynthia; Rajan, Priya; Vidovich, Mladen I.
Abstract : Acute myocardial infarction (AMI) during pregnancy or the early postpartum period is rare, but can be devastating for both the mother and the fetus. There have been major advances in the diagnosis and treatment of acute coronary syndromes in the general population, but there is little consensus on the approach to diagnosis and treatment of pregnant women. This article reviews the literature relating to the pathophysiology of AMI in pregnant patients and the challenges in diagnosis and treatment of ST‐elevation myocardial infarction (STEMI) in this unique population. From a cardiologist, maternal–fetal medicine specialist, and anesthesiologist's perspective, we provide recommendations for the diagnosis and management of STEMI occurring during pregnancy.